PEMILU DAN PARTAI POLITIK DI INDONESIA: Menanti Kebangkitan Partai Politik Islam di Tahun 2019 - Kiki Mikail (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2015)
Indonesian democratic transition in the post-reform era has change the feature of Indonesia's politics. During the New Order, the power of Islam politics had been experiencing fluctuations and dynamics. In the early New Order, Islam was marginalized from the state. In the meantime Islam found many difficulties in evolving social political ideas because of the repressive new order regime. But the most interesting thing of Indonesian political is the dominance of nationalist political parties in every election even though the majority of Indonesian people are Muslim. However, its interesting to look forward how is the oppurtunity of islamic political parties in 2019 election?